Analisa Pengaruh Bentuk Sudut Pada Baja Castellated Dengan Menggunakan Metode Finite Element - Aa Santosa (Jurnal Poli-Teknologi, 2020)
This study examines Kastella beams with cantilever structures using a non-prismatic profile to optimize the steel cross section in resisting external loads. In this study IWF 2500×250×20 steel profile was used. Analysis using finite element with 360 computer fusion program which is a product of Autodesk, as a calculation program to determine the value of the voltage and displacement that occurs in the beam. The process of making castella steel is by perforating the steel profile I into a hexagon with an angle that varies from 45º to 70º, or by cutting the steel profile and then reassembling it by welding it. The research was carried out using 45o and 60o tilt angles, it aims to determine the maximum tilt angle in terms of strength that can withstand loads, both stress and displacement. The simulation process is carried out using a 2000 N load, using A36 material. Based on the research results obtained parameters in the form of stress and displacement. The stresses on castella steel with a slope angle of 45o and 60o are 0.70 Mpa and 0.71 Mpa, respectively. The displacement of the castella steel with a tilt angle of 45o and 60o is 0.002 mm and 0.019 mm, respectively. The results showed that the castella beam with smaller hole angular dimension variations resulted in lower stress values in the structure and the remaining cutting in the optimal test specimen, but produced a large displacement value.